A PROSE REDACTION OF THE PRICK OF CONSCIENCE PART VI IN BODLEIAN LIBRARY, MS LAUD MISC. 23. - WOOD, SARAH (Medium Aevum, 2011)
The article discusses an English prose manuscript describing the various pains of hell (POH), located in the University of Oxford's Bodleian library. According to the author, the text is a prose redaction of Part VI of the text "The Prick of Conscience" (POC). Topics discussed include the use of quotations in both texts, compilations, and copying errors.